Spermidine improves gut barrier integrity and gut microbiota function in diet-induced obese mice - Ma, Lingyan; Ni, Yinhua; Wang, Zhe; Tu, Wenqing; Ni, Liyang; Zhuge, Fen; Zheng, Aqian; Hu, Luting; Zhao, Yufeng; Zheng, Liujie; Fu, Zhengwei (Gut microbes, 2020)
Obesity is associated with impaired intestinal barrier function and dysbiosis of the gut microbiota. Spermidine, a polyamine that acts as an autophagy inducer, has important benefits in patients with aging-associated diseases and metabolic dysfunction. However, the mechanism of spermidine on obesity remains unclear. Here, we show that spermidine intake is negatively correlated with obesity in both humans and mice. Spermidine supplementation causes a significant loss of weight and improves insulin resistance in diet-induced obese (DIO) mice. These effects are associated with the alleviation of metabolic endotoxemia and enhancement of intestinal barrier function, which might be mediated through autophagy pathway and TLR4-mediated microbial signaling transduction. Moreover, spermidine causes the significant alteration of microbiota composition and function. Microbiota depletion compromises function, while transplantation of spermidine-altered microbiota confers protection against obesity. These changes might partly be driven by an SCFA-producing bacterium, Lachnospiraceae NK4A136 group, which was decreased in obese subjects and subsequently increased by spermidine. Notably, the change of Lachnospiraceae NK4A136 group is significantly correlated with enhanced gut barrier function induced by spermidine. Our results indicate that spermidine supplementation may serve as a viable therapy for obesity.